2020
DOI: 10.3390/ijms21228532
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Functional Proteomics in Gastrointestinal Cancers- a Path towards the Identification of Candidate Diagnostic, Prognostic, and Therapeutic Molecular Biomarkers

Abstract: Gastrointestinal (GI) cancer remains one of the common causes of morbidity and mortality. A high number of cases are diagnosed at an advanced stage, leading to a poor survival rate. This is primarily attributed to the lack of reliable diagnostic biomarkers and limited treatment options. Therefore, more sensitive, specific biomarkers and curative treatments are desirable. Functional proteomics as a research area in the proteomic field aims to elucidate the biological function of unknown proteins and unravel the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 124 publications
(144 reference statements)
0
8
0
Order By: Relevance
“…The proteomic studies could be of two types: expression proteomics and functional proteomics. The studies that focus on the upregulation and down-regulations of proteins are the expression proteomics, whereas the studies that focus on the molecular mechanism and the unraveling of the biological functions of novel proteins are called the functional proteomics study [ 75 ]. Like the proteomic studies conducted on bulk tissues, which is not the scope of this discussion, single-cell separation methods, especially LCM, are also employed to understand the expression and functional proteomics of PC.…”
Section: Impact Of Lcm On Pancreatic Cancer Researchmentioning
confidence: 99%
“…The proteomic studies could be of two types: expression proteomics and functional proteomics. The studies that focus on the upregulation and down-regulations of proteins are the expression proteomics, whereas the studies that focus on the molecular mechanism and the unraveling of the biological functions of novel proteins are called the functional proteomics study [ 75 ]. Like the proteomic studies conducted on bulk tissues, which is not the scope of this discussion, single-cell separation methods, especially LCM, are also employed to understand the expression and functional proteomics of PC.…”
Section: Impact Of Lcm On Pancreatic Cancer Researchmentioning
confidence: 99%
“…To study these observed beneficial effects of CBD on human skin, researchers performed two further studies on human keratinocytes cultured in two-and three-dimensional (3D) systems [112,113]. Three-dimensional cell culture efficiently resembles the in vivo environment and provides valuable insight into the effects of CBD on human skin [60,114]. Three-dimensional cell culture showed that exposing cells to UVA and UVB altered the expression of 456 and 217 proteins, respectively.…”
Section: Proteomic Studies On Cannabidiolmentioning
confidence: 99%
“…Advances in high throughput technologies such as genomics, transcriptomics, proteomics and computational modeling have paved the way for better insights into the molecular pathways in disease and health. Proteomics studies, in particular, have attracted significant attention as they are able to determine protein abundance and regulation, changes, proteinprotein interactions and impact on post-translational modifications [60][61][62][63]. Here, we provide a comprehensive literature review of proteomic studies performed in the field, with respect to the therapeutic and toxicological properties of cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…Of the common organs that cause distant metastases, the liver is the most frequent site (59%), except for regional lymph nodes [ 5 ]. The precise mechanism of metastasis to distant organs, including the liver, that fundamentally undermines cancer therapeutic strategies, is not well-understood [ 6 ]. Therefore, finding diagnostic biomarkers and therapeutic targets that reliably determine liver metastases is an urgent task.…”
Section: Introductionmentioning
confidence: 99%